A new species of Pseudostomella (Gastrotricha: Macrodasyida: Thaumastodermatidae) from a sandy beach of Kerala, India - Priyalakshmi, G.; Menon, N. R.; Todaro, M. Antonio (Zootaxa, 2007)
During an interstitial faunal survey along the south-west coast of Kerala, India, gastrotrich fauna were found in abundance. Together with species of the genera Xenotrichula, Halichaetonotus and Tetranchyroderma, were present several undescribed thaumastodermatid gastrotrichs belonging to the buccal palp bearing genus Pseudostomella. Adults of the new species are characterized by the following traits: total body length of about 300 μ m; cuticular armature made up of medium sized pentancres covering the entire dorsolateral surface; pre-buccal, grasping palps bearing five, large papillae dorsally and 4-6 smaller papillae ventrally; adhesive apparatus made up of six anterior, 22-24 ventrolateral, two dorsolateral and six posterior adhesive tubes; caudal organ pear-shaped; frontal organ spherical. Pseudostomella cheraensis sp. nov. is the fourth taxon of the genus known from India; however, all the previous species reported hitherto from India have tetrancres instead of pentancres.